2017
DOI: 10.3389/fmicb.2016.02130
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Viruses Replicate Productively in Mouse Mastocytoma Cells (P815) and Trigger Pro-inflammatory Cytokine and Chemokine Production through TLR3 Signaling Pathway

Abstract: The influenza A viruses (IAVs) cause acute respiratory infection in both humans and animals. As a member of the initial lines of host defense system, the role of mast cells during IAV infection has been poorly understood. Here, we characterized for the first time that both avian-like (α-2, 3-linked) and human-like (α-2, 6- linked) sialic acid (SA) receptors were expressed by the mouse mastocytoma cell line (P815). The P815 cells did support the productive replication of H1N1 (A/WSN/33), H5N1 (A/chicken/ Henan/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 53 publications
2
32
1
Order By: Relevance
“…Furthermore, MCs release type I interferons and C-X-C motif chemokine following toll-like receptor 3 activation. These data confirmed that viruses replicate in MC and this virus-MC interaction essentially contributes to the pathogenesis of influenza viruses [10]. However, the detailed response of MCs to these influenza viruses is incompletely understood.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, MCs release type I interferons and C-X-C motif chemokine following toll-like receptor 3 activation. These data confirmed that viruses replicate in MC and this virus-MC interaction essentially contributes to the pathogenesis of influenza viruses [10]. However, the detailed response of MCs to these influenza viruses is incompletely understood.…”
supporting
confidence: 65%
“…Research has confirmed that MCs may lack critical factors essential for the replication of H1N1 [9]. However, in our study we found that P815 cells expressed both a-2, 3-and a-2, 6-linked SA receptors to initiate IAV (H1N1, H5N1, and H7N2) infection [10]. Furthermore, MCs release type I interferons and C-X-C motif chemokine following toll-like receptor 3 activation.…”
contrasting
confidence: 54%
“…TLR3 engagement in mouse and human MCs does not induce degranulation but can inhibit degranulation in some experimental settings . TLR3‐mediated MC activation elicits the production of type I interferon (IFNα/β), IL‐6, TNFα, IFNγ and the chemokines CCL2, CCL4, CCL5, CXCL1, CXCL2, and CXCL10 . This profile of secretion allows MCs to recruit pro‐inflammatory cells such as CD8 + T cells .…”
Section: Pattern Recognition Receptorsmentioning
confidence: 99%
“…Since then, it has become well known for its potential to cause global pandemics in humans and mammals at all ages with considerable risks of morbidity and high fatality rates; it is now considered a growing threat to public health around the world. 45,46 To date, it has been classified as a List A disease by the World Organisation for Animal Health (OIE) and as a Category 1 animal disease in China. A variety of antiviral drugs and vaccines have been adopted to prevent and control influenzainduced illness.…”
Section: Discussionmentioning
confidence: 99%